Community health and wellness needs assessment : a step-by-step guide - Nardi, Deena A.; Petr, Josy M. (Clifton Park, NY : Thomson/Delmar Learning, 2003)
Introduces health and wellness needs assessment as a holistic process that encompasses physical, psychological, social, spiritual, environmental, and economic aspects of life in the US. Providing step- by-step guidance through a systematic assessment, this book is suitable for any nurse evaluating the health of a community. Annotation copyrighted by Book News, Inc., Portland, OR.
Introduction to health and wellness needs assessment -- Steps of the community health and wellness needs assessment process -- Assessing physical health and wellness -- Assessing mental health and wellness -- Assessing maternal, child, and family health and wellness -- Assessing community health and wellness -- Analyzing indicators and using the analysis -- Resources for data gathering and comparison.
Includes bibliographical references and index.
Keywords: COMMUNICTY HEALTH SERVICES; NEEDS ASSESSMENT; HEALTH PROMOTION